Gestão integrada da doença: uma abordagem experimental de gestão em saúde - Escoval, Ana (2010)
The health systems are faced with new paradigms, on one hand in the healthcare services delivered to the populations, and on the other hand, in the need to control costs in the health sector, forcing organizations to adapt and provide the most appropriate response to the individuals growing needs. The magnitude of this problem, in terms of public health, requires the adoption of a directed, targeted, planned and integrated action, based on clear and well defined strategies in order to obtain health gains, improving the quality of care and streamlining the costs. In Portugal, the application of those principles forming the basis of the disease management models, led to the Integrated Disease Management model which, apart from the clinical management of the disease, also incorporates the healthcare delivery structure reorganization, a specific financing model based on an information system that allows the process monitoring and evaluation. The development of Integrated Disease Management models is a central strategy and a tool for improving healthcare delivery, more effectively and efficiently, and can even be an important and permanent vehicle of information for health decision support. Therefore, it is important to promote a concerted action towards achieving a precise intervention, mobilizing the resources, improving the health status, quality of life and the overall patients’ wellbeing. This action means increasing collaboration and coordination of the different levels of care, offering integrated healthcare services with high quality levels regarding prevention, diagnosis, treatment, rehabilitation and monitoring.